2021
DOI: 10.1038/s41598-021-92023-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing reveals a novel homozygous mutation in the COQ8B gene associated with nephrotic syndrome

Abstract: Nephrotic syndrome arising from monogenic mutations differs substantially from acquired ones in their clinical prognosis, progression, and disease management. Several pathogenic mutations in the COQ8B gene are known to cause nephrotic syndrome. Here, we used the whole-exome sequencing (WES) technology to decipher the genetic cause of nephrotic syndrome (CKD stage-V) in a large affected consanguineous family. Our study exposed a novel missense homozygous mutation NC_000019.9:g.41209497C > T; NM_024876.4:c.74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Of these cases, 75% (33/44) had their onset before or at the age of 10 years (range 10 days to 25 years). The median age of onset in the Chinese population was earlier than that of non-Chinese patients ( 1 , 13 15 , 17 , 19 , 25 29 ) ( Figure 4A ). We also found that the age of onset in the Chinese population was younger than that in other Asian populations, but the difference was not significant ( P = 0.051; Figure 4B ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Of these cases, 75% (33/44) had their onset before or at the age of 10 years (range 10 days to 25 years). The median age of onset in the Chinese population was earlier than that of non-Chinese patients ( 1 , 13 15 , 17 , 19 , 25 29 ) ( Figure 4A ). We also found that the age of onset in the Chinese population was younger than that in other Asian populations, but the difference was not significant ( P = 0.051; Figure 4B ).…”
Section: Resultsmentioning
confidence: 95%
“…Cases without data on follow-up and patient outcomes were excluded ( 1 , 12 – 14 ). A total of 18 cases were included for subsequent analysis ( 15 19 ). The median follow-up time was 24 (IQR 17.8–95.0) months, up to 180 months.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that the resultant deficit in CoQ 10 levels impairs the mitochondrial respiratory chain and causes podocyte injury. Reinforcing the importance of mitochondrial health CoQ 10 biosynthesis in podocyte biology, in humans, mutations in COQ6 and COQ8B have also been associated with steroid-resistant nephrotic syndrome and collapsing glomerulopathy [38,39],…”
Section: Genetic and Drug-induced Forms Of Collapsing Glomerulopathymentioning
confidence: 97%
“…It is thought that the resultant deficit in CoQ 10 levels impairs the mitochondrial respiratory chain and causes podocyte injury. Reinforcing the importance of mitochondrial health CoQ 10 biosynthesis in podocyte biology, in humans, mutations in COQ6 and COQ8B have also been associated with steroid-resistant nephrotic syndrome and collapsing glomerulopathy [38,39], and in the kd/kd mouse, truncating mutations in the prenyltransferase-like mitochondrial protein (PLMP) result in mitochondrial defects and collapsing glomerulopathy [40]. The bisphosphonate medications, such as pamidronate, are also thought to impair mitochondrial function and have been linked to collapsing glomerulopathy [41].…”
Section: Clinical Associations With Collapsing Glomerulopathy and Les...mentioning
confidence: 99%
“…Salviati et al found that the genotypephenotype correlation of COQ8B mutation was not clear, and the mutation might affect the interaction between COQ8B and other COQ proteins (12). Singh et al assumed that COQ8B (p.Asp250Asn) undermined the interaction of proteins by targeting COQ5, which is one of the important components in the COQ giant complex, resulting in a progressive deterioration from normal renal function to renal failure (13). The minimum age of such patients was 1 year and 1 month.…”
Section: Treatment and Follow-upmentioning
confidence: 99%